Effects of solvents and penetration enhancers on transdermal delivery of thymoquinone: permeability and skin deposition study - Anika Haq; Bozena Michniak-Kohn (Taylor & Francis Group, 2018)
Thymoquinone (TQ) is a quinone-based phytochemical that was first identified in 1963 in Nigella sativa (black cumin seed) by El-Dakhakhany. Based on the ideal characteristics of transdermal delivery, TQ is potentially an attractive candidate for transdermal drug delivery. The aim of this study was to investigate the feasibility of transdermal delivery of TQ and to assess the effect of an ethanol and propylene glycol donor solvent system along with various compositions of receptor solvents. The effects of penetration enhancers on the in vitro skin permeation and TQ skin absorption were studied using human cadaver skin in Franz diffusion cells. The permeation of saturated solutions of TQ was investigated with 5% v/v of each of the following enhancers: Azone (laurocapram), Transcutol® P (Tc), oleic acid, ethanol, Polysorbate 80 (Tween 80), and N-methyl-pyrrolidone (NMP). The results indicated that Azone, oleic acid, and Tc were able to provide adequate TQ flux and may be the agents of choice for use in a novel transdermal formulation of TQ. These penetration enhancers were also able to generate TQ reservoirs in the skin that may be useful to provide sustained release of TQ from the stratum corneum over longer periods of time.